1975
DOI: 10.1103/physrevc.11.1767
|View full text |Cite
|
Sign up to set email alerts
|

High-spin rotational states inHf169from theTb

Abstract: High-spin level. s of the deformed nucleus Hf were deduced from y-ray spectroscopy, both in beam following the heavy-ion reaction 59Tb(~4N, 4ny) 9Hf and out of beam from P decay of 9Ta. The half-l. ife of 9Ta was remeasured as 4.7 + 0.7 m. Three rotational bands were assigned in Hf: & [523] ground band, up to spin 2, 2 [512], 59.1 keVbandhead, up to spin +2, . and g [642], p bandhead at 28.80 keV, up to spin~2 and tentatively up to spin -,. The 2 bandhead of the 2 [642] band is isomeric and decays with a half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The resulting level scheme is shown in Fig. 3 [15], was not seen. This absence was also reported recently by the Manchester group [16].…”
Section: Data Analysis and Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The resulting level scheme is shown in Fig. 3 [15], was not seen. This absence was also reported recently by the Manchester group [16].…”
Section: Data Analysis and Resultsmentioning
confidence: 97%
“…The positiveand negative-parity bands in ' Hf have been classified [15] as -, ' + [642] and -, ' [523] neutron bands, respectively. The level scheme of ' Hf has been extended significantly in the present work by employing the y-y coincidence technique.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate region (Yb, Hf and W isotopes) has also been investigated by this "blocking" technique. It has experimentally been observed that backbending is inhibited in the vi 13/2 mixed positive-parity bands for odd-neutron isotopes of Yb [11,12], Hf [13,14] and W [15,16], but not in bands based on other neutron orbits. For the odd-proton nuclei, experiments show that backbending is inhibited in various 7~h9/2 decoupled bands in 163'165Tm [17,18] 0340-2193/81/0299/0149/$02.60 and 167'169Lu [19,20], but not in bands based on other proton orbits.…”
Section: Introductionmentioning
confidence: 99%
“…5), we suggest possible reasons why backbending is delaYed for the ~h9/2 proton bands in the odd -Z, N=96 isotones 16STm and 167Lu. The experimental data on the energy levels of the N =96 and 97 isotones which are used in the present paper are extracted from the following references: 164Er [25][26][27]; a65Er [28]; 165Tm [18]; 166yb [29][30][31]; 167yb [32]; 167Lu [19]; 16SHf [29,33,34]; 169Hf [13]; 17~ [35]. The lifetimes of members of the g.s.…”
Section: Introductionmentioning
confidence: 99%